Intracranial hypertension in Africans with cerebral malaria. Issue 3 (1st March 1997) - Newton, C R J C; Crawley, J; Sowumni, A; Waruiru, C; Mwangi, I; English, M; Murphy, S; Winstanley, P A; Marsh, K; Kirkham, F J
Abstract : The causes of death and neurological sequelae in African children with cerebral malaria are obscure. Intracranial pressure (ICP) was monitored and cerebral perfusion pressure (CPP) calculated in 23 Kenyan children with cerebral malaria. Four children had severe intracranial hypertension (ICP >40 mm Hg, CPP <40 mm Hg): two died, one with an ICP of 158 mm Hg and signs of transtentorial herniation, the other one with an ICP of 42 mm Hg and cardiorespiratory arrest. The other two survived with severe neurological sequelae. Nine had intermediate intracranial hypertension (ICP >20 mm Hg, CPP <50 mm Hg) and 10 had mild intracranial hypertension (maximum ICP 10–20 mm Hg); all survived without severe sequelae. Mannitol controlled the ICP in children with intermediate intracranial hypertension, but it did not prevent the development of intractable intracranial hypertension in children with severe intracranial hypertension. Intracranial hypertension is a feature of Kenyan children with cerebral malaria and severe intracranial hypertension is associated with a poor outcome.